Dantrolene for Generalized Tetanus in Pediatrics: A Case Report and Review of Treatment Options. Issue 4 (3rd July 2022) - Khan, Natasha; Zulfiqar, Fizza; Hollander, Leanna; Johnson, Travis; Lamsal, Riwaaj
Abstract: There are only sporadic cases of tetanus in children in the United States. We describe an unimmunized child with generalized tetanus who required nearly a month of mechanical ventilation with analgesia, sedation, and neuromuscular blockade. Dantrolene showed benefit in spasm control and patient comfort when used in combination with other drugs.